Task-specific ionic liquids: Applications in sample preparation and the chemistry behind their selectivity - Llaver, Mauricio (2022)
Task-specific ionic liquids (TSILs) represent a sub-family of ionic liquids characterized by their high specificity towards a target analyte or group of analytes. This characteristic has made them valuable tools for sample preparation, where selectivity represents a key aspect, especially when other species represent a significant source of interference or when non-specific detectors are used. This review presents an overview of TSILs applications for sample preparation from the last ten years, with a special emphasis on their use as liquid-liquid microextraction solvents or as functionalizing agents for sorbents applied to solid-phase microextractions. TSILs applications for the treatment of environmental, food and biological samples are reviewed, including reports devoted to speciation analysis, a relevant trend in recent years regarding elemental studies. Additionally, focus is made on the ?task-specificity? of the presented TSILs, including a description of the chemical characteristics that made them selective towards the studied analytes. Finally, future trends and gaps to be covered in the field are also discussed.